Feminist Action Research in Mental Health: A Practical Guide [Book Review] - Appleby, Jo (Aotearoa New Zealand Association of Social Workers, 2026)
Review of: Jarldorn, M., Moulding, N., & Deuter, K. (Eds.) (2026). Feminist action research in mental health: A practical guide. Palgrave Macmillan. ISBN 978-3-032-04405-1, pp.141, hardback, NZD90.56.